Lord Macaulay's Recommendation on Education During British Rule in India: An Analysis - Maruti B. Gowda, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
The paper examines the impact of Macaulay's Minute on Indians and on the Indian education. The impact may be seen in two forms, namely immediate impact and long term impact. This in turn helped in the material prosperity, social reform, rise of national consciousness, independence movement and finally in achieving Independence. The paper examines the inadequacies of the Indian Education Commission examined the education and suggested some improvements. Thoroughly it made suggestions for removing inadequacies. The paper explores the reason from maintaining English as the medium of education at the higher level is that it is a compulsion as well as the necessity.
Keywords: Education; Commission; Literature; Knowledge; System; British; Rule; Recommendation